Passivity-based fuzzy logic approach for optimal power extraction from PMSG-wind energy conversion - Chaturvedi, Pallavi; Palwalia, Dheeraj Kumar (Institute of Advanced Engineering and Science, 2024)
The preference for permanent magnet synchronous generators (PMSGs) in wind energy conversion systems (WECS) is due to their reliability, compactness, and efficiency. However, designing controllers for PMSG-WECS faces challenges from parameter uncertainties, nonlinearity, and grid integration. To address this, a novel passivity-based nonlinear controller (PBNC) is proposed to precisely track speed and torque. This unique PBNC employs a damped approach to address nonlinearity and integrates a fuzzy logic controller (FLPBNC) for robustness. The chosen strategy shapes energy dynamics using Lyapunov functions. The addition of damping elements ensures Lyapunov stability condition and boosts convergence while keeping the energy functions positive. The system design involves linking passive mechanical and electrical parts in a feedback loop. Meanwhile, for grid integration, a proportional-integral (PI) controller manages DC-link voltage and active power supply to the grid. MATLAB/Simulink simulations confirm the effectiveness of the proposed approach compared to conventional methods.